2006
DOI: 10.1007/s00018-006-6138-z
|View full text |Cite
|
Sign up to set email alerts
|

Unscheduled CDK1 activity in G1 phase of the cell cycle triggers apoptosis in X-irradiated lymphocytic leukemia cells

Abstract: Cyclin-dependent kinase 1 (CDK1) is a major component of the cell cycle progression engine. Recently, several investigations provided evidence demonstrating that unscheduled CDK1 activation may also be involved in apoptosis in cancerous cells. In this article, we demonstrate that X-ray irradiation induced G1 arrest in MOLT-4 lymphocytic leukemia cells, the arrest being accompanied by reduction in the activity of CDK2, but increased CDK1 activity and cell apoptosis in the G1 phase. Interestingly, this increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Exposure of cells to ionizing radiation delays the normal progression of cell cycle, and significant arrest might occur in G 1 , S, or G 2 phases that reflect induction of cellular processes assisting the irradiated cell to repair induced damages (Iliakis et al, ). Similar to current results, many studies have indicated delay in G 1 phase of the cell cycle upon X‐ray exposure, for instance in human glioma, leukemia, and holangiocarcinoma cells (Li et al, ; Wu et al, ; Hemaltulin et al, ). It has also been reported that auraptene, in toxic concentrations, induced sub‐G 1 peak in the flow cytometry histogram of breast, gastric, and prostate cancer cells (Mousavi et al, ; Moon et al, ; Lee et al, ) and inhibited cell proliferation by down regulating several genes involved in cell cycle control such as cyclin D1 , E2F1 , CDC2, and UHRF1, which promote G 1 to S phase transition (Krishnan and Kleiner‐Hancock, ).…”
Section: Discussionsupporting
confidence: 89%
“…Exposure of cells to ionizing radiation delays the normal progression of cell cycle, and significant arrest might occur in G 1 , S, or G 2 phases that reflect induction of cellular processes assisting the irradiated cell to repair induced damages (Iliakis et al, ). Similar to current results, many studies have indicated delay in G 1 phase of the cell cycle upon X‐ray exposure, for instance in human glioma, leukemia, and holangiocarcinoma cells (Li et al, ; Wu et al, ; Hemaltulin et al, ). It has also been reported that auraptene, in toxic concentrations, induced sub‐G 1 peak in the flow cytometry histogram of breast, gastric, and prostate cancer cells (Mousavi et al, ; Moon et al, ; Lee et al, ) and inhibited cell proliferation by down regulating several genes involved in cell cycle control such as cyclin D1 , E2F1 , CDC2, and UHRF1, which promote G 1 to S phase transition (Krishnan and Kleiner‐Hancock, ).…”
Section: Discussionsupporting
confidence: 89%
“…The progression of the cell cycle and the execution of apoptosis have been demonstrated to be opposing processes (31)(32)(33). We found that the unscheduled activation of cyclin-dependent protein kinase 1 (CDK1/CDC2) was involved in the execution stage of apoptosis in MOLT-4 cells induced by X-ray irradiation (17). Others have shown that sublethal damage leading to a small quantity of caspase activation can protect neurons from more severe damage (34).…”
Section: Apoptosis Pattern Varies With Changes In the Cell Cyclementioning
confidence: 85%
“…The phase specificity of apoptosis might represent the point at which the accumulated cell damage overwhelms the driving force for proliferation in a cell, and the cell consequently enters apoptosis. This implies that, at this point, the cell cycle machinery and the apoptotic process are acting at cross purposes (17).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B1/CDK1 is known to be responsible for initiating mitochondria-mediated apoptosis under cell damage conditions by phosphorylation of several pro-and antiapoptotic proteins (37, 219,229). CDK activity is involved in the mitochondrial translocation of Bax, which plays an important role in the mitochondrial membrane permeability transition during apoptotic progression (47).…”
Section: Cyclin B1/cdk1 In Mitochondria-mediated Apoptosismentioning
confidence: 99%